(untitled) (Contemporary Journal of Social Science Review, 2025)
Leader Member Exchange (LMX) and innovative work behavior (IWB) both are important areas to be considered by managers and have been point of discussion of researchers for several years. Similarly, employee voice behavior (EVB) and perceived organizational behavior (POS) both are essential essentially required at workplaces. The aim of the current research study is to test the impact of LMX Quality on IWB with the mediating role of EVB and the moderating role of POS. Employees working in IT based companies located in Rawalpindi and Islamabad were chosen. A purposive sampling technique was used to collect data from 600 respondents using well-structured questionnaires. Perception from diverse groups of employees across multiple projects shows that high-quality Leader-Member exchange promotes innovative work behavior by increasing employee voice behavior and perceived organizational support. Findings revealed that LMX quality and EVB have a significant impact on Innovative Work Behavior, with positive results. Despite the growing significance of innovative work behavior in the IT project-based industry, few studies have focused on the impact of Leader-Member Exchange quality on this phenomenon. Additionally, the perceived organizational support of the individual acts as a moderator, and employee voice behavior serves as a mediator in this interaction.